Decrease in high on-treatment platelet reactivity (HPR) prevalence on switching from clopidogrel to prasugrel: insights from the switching anti-platelet (SWAP) study - Saucedo, Jorge F; Angiolillo, Dominick J; DeRaad, Roger; Frelinger, 3rd, Andrew L; Gurbel, Paul A; Costigan, Timothy M; Jakubowski, Joseph A; Ojeh, Clement K; Duvvuru, Suman; Effron, Mark B (Thrombosis and haemostasis, 2013)
The prevalence of high platelet reactivity (HPR) in patients who have switched from clopidogrel to prasugrel during maintenance phase after an acute coronary syndrome (ACS) event is unknown. Therefore, the effect of switching from clopidogrel to prasugrel on the prevalence of HPR was evaluated. This analysis from the previously reported SWAP (SWitching Anti Platelet) study assessed HPR at baseline, 2 and 24 hours, and seven days after switching from clopidogrel to prasugrel maintenance dose (MD), with or without a prasugrel loading dose (LD) using four definitions: maximum platelet aggregation (MPA) >65% (primary endpoint), MPA >50%, P2Y12 reaction units (PRU) >235, and platelet reactivity index (PRI) ≥ 50%. A total of 95 patients were available for analysis; 56 patients provided DNA for genetic assessments of cytochrome P450 (CYP) 2C19. There were 26 (27.4%) patients with HPR at the end of the clopidogrel run-in (defined as MPA >65%). The HPR prevalence varied by each definition and ranged from 19% (PRU >235) to 68% (PRI ≥ 50 %). A significantly higher HPR prevalence was observed during clopidogrel versus the combined prasugrel therapy groups at seven days as measured by MPA >65% (21.2% vs. 4.5%, p<0.05), PRU >235 (18.8% vs. 0%, p=0.001), and PRI ≥ 50 % (66.7% vs. 7.9%, p<0.0001). There was a significantly higher percentage of subjects carrying at least one reduced function allele with HPR measured by MPA >65% (p=0.02) or PRU >235 (p=0.05) than non-carriers with HPR. Switching ACS patients during maintenance clopidogrel therapy to prasugrel with or without an LD is associated with a reduced HPR prevalence and may provide an alternative strategy to treat patients with HPR, independent of CYP2C19 genotype.